Factors associated with birthweight decline in Japan (1980-2004) - Noriko Kato; Catherine Sauvaget; Honami Yoshida; Tetsuji Yokoyama; Nobuo Yoshiike (BMC, 2021)
Abstract Background Birthweight has been declining consistently for more than 30 years in Japan. This rapid rise in low birthweight is one of the worst among the countries of the Organization for Economic Co-operation and Development. We examined potential determinants of birthweight decline in Japan. Methods We used population-based birth certificate data from vital statistics records and retrieved 40,968,266 birth certificates of neonates born between 1980 and 2004. We analyzed time trends using linear regression analysis in examining whether the decline in birthweight could be explained by obstetrical variables such as gestational age and multiple gestations. Results From 1980 to 2004, we observed a decline in mean birthweight with a yearly effect of − 8.07 g, which became steeper after 1985, persisted until 1999, and plateaued thereafter. After adjusting for gestational age, gender, birth order, multiple gestations, and fathers' age, the yearly effect between 1980 and 2004 persisted at − 5.13 g. Conclusion Recent decreases in birthweight among Japanese neonates were not fully explained by trends in gestational age, gender, birth order, multiple gestations, and fathers' age. Thus, additional factors such as pre-pregnancy maternal body mass index (BMI) and maternal diet should be considered. Reducing the rate of induced deliveries and improving the BMI or diet of young women should be a public health priority.